Les identits rgionales et la dialectique Sud-Sud en question - Marouf, Nadir, 1940- (Book collections on Project MUSE., 2007)
This book highlights the importance of Pan-Africanism in view of reasserting its vital role in the economic integration of the continent. For Africans to coexist and aspire to a much needed dynamic and social community, there is a need for a common understanding of their shared histories and projects. The contributions analyse regional identities that deriver from an observed sycretism between traditional culture, Islamic religion and modernity. The example of interregional relations is tangible proof of the difficult negotiation of imposed international axiological constraints. From this perspective, the new partnership between the North and the South ought to be the responsibility of all and sundry, in which social or state actors are capable of communicating and putting forward their various rationalities for discussion. In this way, the South-South dialectic will find its place: regionalisation will as such promote solidarity between peoples and the reinvention of great democratic values.